O2 Changes in alcohol-related liver disease admissions over the time of minimum unit pricing of alcohol: the GRI Q4 study. (28th September 2020) - Chaudhary, Sardar; Mackey, William; Duncan, Katherine; Forrest, Ewan
Abstract : Introduction and Aim: Minimum unit price (MUP) of 50 pence per unit of alcohol was introduced in Scotland on the 1st of May 2018. This was one of several measures which hoped to reduce alcohol harm and alcohol-related liver disease (ArLD) in particular. Standard discharge coding for ArLD is not sufficiently accurate to determine differences between variable clinical presentations. We aimed to assess the effect of MUP on the presentation of patients with ArLD to Glasgow Royal Infirmary (GRI). Methods: The medical records of all patients discharged from the Gastroenterology/Liver wards at GRI in the fourth quarter (Q4) of the years 2015–2019 were reviewed (pre-MUP 2015–17; post-MUP 2018–19). All patients with ArLD were identified and admission data were collected retrospectively detailing clinical features of liver disease, blood test results and recent drinking history. Over this time there has been no change to the placement of ArLD patients in GRI. The National Institute of Alcohol Abuse and Alcoholism definition for alcoholic hepatitis (AH) was used. MELD scores were determined for all patients. Active drinking was defined as alcohol use within 8 weeks of admission. The 90-day mortality and readmission rates were assessed. Results: In total 1875 inpatient episodes were reviewed (1164 pre-MUP; 711 post-MUP) of which 377 were with ArLD (241 pre-MUP; 136 post-MUP). Overall, the mean number of ArLD in-patient episodes fell (80.3 pre-MUP; 68 post-MUP) with a similar fall in the individual patients in each quarter (70.7 pre-MUP, 53.5 post-MUP). The proportion of active drinkers was lower post-MUP (64.7%) compared with pre-MUP (70.5%). There were no differences in the proportion of patients presenting with ascites (45.2% cf. 47.8%), encephalopathy (21.2% cf. 24.3%) or AH (18.3% cf. 19.1%) pre- and post-MUP. However, there was a reduction in presentations with acute upper GI bleeding (AUGIB): 15.8% cf. 7.4%: p=0.02; odds ratio 0.42. The overall severity of liver disease remained unchanged (mean MELD 16 for both time periods). The 90-day mortality (12.4% cf. 13.2%) and readmission (48.5% cf. 54.4%) rates were not significantly different pre- and post-MUP. Conclusion: Since the introduction of MUP there has been a reduction in the absolute numbers of ArLD in-patient episodes and number of individual patients involved at GRI. However the pattern of clinical presentation was largely unaffected other than a reduction in the proportion of patients presenting with AUGIB. The overall ArLD severity, readmission rates and 90-day mortality were similar pre- and post-MUP.